2021
DOI: 10.3390/life11111236
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Expanding Pulmonary Rehabilitation Services

Abstract: Pulmonary rehabilitation is a strongly recommended and effective treatment for people with chronic lung disease. However, access to pulmonary rehabilitation is poor. Globally, pulmonary rehabilitation is accessed by less than 3% of people with chronic lung disease. Barriers to referral, uptake and completion of pulmonary rehabilitation are well documented and linked with organizational, practitioner and patient-related factors. Enhancing the knowledge of health care professionals, family carers, and people wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 76 publications
(106 reference statements)
1
22
0
Order By: Relevance
“…Almost half of the study participants perceived ‘patients might refuse the referral’ as a major barrier to refer COPD patients to PR which is in accordance with recent study included physicians and concluded that 46% perceived patients refuse referral is a major barrier 13. This may be due to the lack of patients’ knowledge about the PR and its benefit to their condition as well as travel distance to PR 19 30 31. Therefore, incorporating patients’ preferences of PR delivery mode and increasing awareness of PR and its benefit among COPD population are needed.…”
Section: Discussionsupporting
confidence: 73%
“…Almost half of the study participants perceived ‘patients might refuse the referral’ as a major barrier to refer COPD patients to PR which is in accordance with recent study included physicians and concluded that 46% perceived patients refuse referral is a major barrier 13. This may be due to the lack of patients’ knowledge about the PR and its benefit to their condition as well as travel distance to PR 19 30 31. Therefore, incorporating patients’ preferences of PR delivery mode and increasing awareness of PR and its benefit among COPD population are needed.…”
Section: Discussionsupporting
confidence: 73%
“…Barriers to referral, uptake and completion of PR are well documented and linked with organisational, practitioner and patient-related factors 31. However, the extent to which the use of a training app can close a gap here must certainly be evaluated in further studies.…”
Section: Discussionmentioning
confidence: 98%
“…The COVID-19 pandemic has highlighted the need of pulmonary rehabilitation, with strong quality assurance to ensure optimal patient outcomes. Properly planned pulmonary rehabilitation programme optimizes respiratory muscle function, improve exercise capacity, reduce dyspnea, improve endurance and enhance health related Quality of life .The ultimate role is to help the patient's active participation or return to family and society (16) . The aim of the study is to check the effectiveness of balloon blowing technique on exercise tolerance , peak expiratory flow rate and quality of life of post COVID-19 survivors .Some studies shows that balloon blowing exercise will be strengthen the expiratory muscles .Patients who performed balloon blowing exercise increased their FVC ,FEV1 , TLC in chronic lung disease (17)…”
Section: Introductionmentioning
confidence: 99%